Penampilan Karakter Kuantitatif dan Korelasi Karakter-karakter pada Galur Tanaman Jagung Hasil Selfing pada Kondisi Lahan Kering - Ni Wayan Sri Suliartini; I Wayan Sutresna; I Wayan Sudika; Novita Hidayatun Nufus; Wa Ode Nuraida (Postgraduate, University of Mataram, 2026)
This study investigates the quantitative characteristics of several generations of self-pollinated lines and the F2 population, as well as the correlation between these characteristics and leaf angle, harvest age, and yield in corn plants. The experiment was carried out in Gumantar village, North Lombok, from May to September 2024, and was designed using a Complete Randomized Block Design with treatments including the F2 population, 15 S1 lines, 15 S2 lines, 15 S3 lines, and 15 S4 lines. The study examined 14 quantitative characteristics. The experimental data were analyzed using analysis of variance. Further testing was conducted using the DMRT test at a 5% level. Correlations between traits were calculated using the Pearson correlation test. The research results demonstrate that the quantitative characteristics of several generations of selfing lines and the F2 population differ, except for ASI and cob diameter. The selfing from the first through fourth generations exhibit lower values compared to the F2 population, with the exceptions of anthesis-tasseling age, silk emergence, and harvest age. Most traits are associated with the medium harvest age category. The yield is correlated with most quantitative characters in the medium to strong category. The selection of plants to be selfed to form the S5 lines and increase yields should use plant height as a selection criterion.